NATIONAL FRANCHISE: SUCCESS AND FAILURE FACTORS - Ulloa Soto, José David (2012)
This paper is aimed at identifying the critical factors that ease or hinder the implementation of the franchise model in Costa Rica by contrasting the criteria from the different participants in the franchise system. The most important variables that affect this transformation from local small business to franchise are summarized at the end of the study.